2017
DOI: 10.1891/0886-6708.vv-d-15-00054
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Stalking: The Impact of Threat Level and Victim Response

Abstract: Because of varying legal definitions across jurisdictions, factors that influence judgments of what constitutes stalking are important to identify. In this study, participants (N = 147) were randomly assigned to read 1 of 4 vignettes involving a hypothetical case of stalking, stemming from a 2 (threat level: explicit vs. implicit) × 2 (victim response: fear vs. anger) between-subjects factorial design. Overall, when the threat was implicit or the victim responded with anger, participants were less inclined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Indeed, in a recent study about stalking perceptions, Uhl, Rhyner, Terrance, and Plumm (2017) concluded that people usually rated vignettes as stalking when the interaction involved fear and explicit threat.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent study about stalking perceptions, Uhl, Rhyner, Terrance, and Plumm (2017) concluded that people usually rated vignettes as stalking when the interaction involved fear and explicit threat.…”
Section: Discussionmentioning
confidence: 99%
“…There is even less information on social perceptions of stalking. Although relatively plentiful in English-speaking countries (Cass and Mallicoat, 2015; Duff and Scott, 2013; Gavin and Scott, 2016; Scott et al, 2010; Scott et al, 2014; Scott et al, 2018; Uhl et al, 2017), the information for continental European countries is scant (De Fazio et al, 2015; Kamphuis et al, 2005; Matos and Sheridan, 2015; Modena Group on Stalking, 2005; Sheridan et al, 2017), particularly measurements of perceptions of stalking based on case scenarios. Given the high prevalence of stalking on university campuses (Baum et al, 2009; Bjerregaard, 2000; Feltes et al, 2012; National Union of Students, 2011), research that explores the perceptions of stalking by university students is merited, because it can highlight prejudices and stereotypes regarding gender and relationships and also inform us about the perceived effectiveness of the criminal justice system.…”
Section: Introductionmentioning
confidence: 99%